Post-Soviet social - Neoliberalism, social modernity, biopolitics - Collier, Stephen J.
"The Soviet Union created a unique form of urban modernity, developing institutions of social provisioning for hundreds of millions of people in small and medium-sized industrial cities spread across a vast territory. After the collapse of socialism these institutions were profoundly shaken - casualties, in the eyes of many observers, of market-oriented reforms associated with neoliberalism and the Washington Consensus. In "Post-Soviet Social", Stephen Collier examines reform in Russia beyond the Washington Consensus. He turns attention from the noisy battles over stabilization and privatization during the 1990s to subsequent reforms that grapple with the mundane details of pipes, wires, bureaucratic routines, and budgetary formulas that made up the Soviet social state. Drawing on Michel Foucault's lectures from the late 1970s, "Post-Soviet Social" uses the Russian case to examine neoliberalism as a central form of political rationality in contemporary societies. This book's basic finding - that neoliberal reforms provide a justification for redistribution and social welfare, and may work to preserve the norms and forms of social modernity - lays the groundwork for a critical revision of conventional understandings of these topics. "